Integrasi Association Rule Mining dan Cost-Plus Pricing untuk Optimasi Paket Produk dan Profitabilitas UMKM - Nasri, Muhammad Haris; Pratama, Gede Yogi; Hammad, Rifqi; Switrayana, I Nyoman; Husaini, Rahayun Amrullah (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics; Vol 11 No 1 (2026): INFORMATICS FOR EDUCATORS AND PROFESSIONAL : JOURNAL OF INFORMATICS (Juni 2026)DO - 10.51211/itbi.v11i1.3886, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy, yet they still face challenges in developing product packages and optimal pricing. This study aims to integrate the Apriori algorithm and the Cost-Plus Pricing method in developing product packages and determining optimal selling prices. The data used are 2,000 MSME sales transactions processed through preprocessing, data transformation, and analysis using the Apriori algorithm with a minimum support of 0.01 and a confidence of 0.4. The results show that 54 frequent itemsets and association rules were obtained with an average support value of 0.564, a confidence of 0.926, and a lift of 1.694. The best rule produces two main product packages, namely the Coffee and Dodol package and the Chicken Special Grill, Plecing Kangkung, and Sambal package. Furthermore, the package prices were determined using the Cost-Plus Pricing method and a profit increase simulation was conducted. The results show that profits increased from 48,293,400 to 53,517,360, representing an increase of 5,223,960. Thus, the integration of these two methods has proven effective in increasing profitability and can be used as a data-driven marketing strategy for MSMEs.